IoT-Based Smart Mangrove Tourism: Innovations in Conservation and Community Empowerment at Petengoran Mangrove - Nurhayu, Winati; Adhha, Nurul; Rahmattullah, Rahmattullah; Amelia, Intan; Tasib, Syahidan Syaean (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
This community service program addressed the challenges of weak financial management and lack of technological innovation in the development of Petengoran mangrove ecotourism in Gebang Village, Lampung. The subject of this program is the Petengoran Mangrove Conservation Group and 35 village residents, including women, youth, and local leaders. The purpose was to strengthen community capacity in managing ecotourism through IoT-based monitoring and digital promotion. The method employed includes training sessions, IoT device installation, digital campaign assistance, pre-test and post-test evaluations, and collaborative mentoring between academia and the community. Results show significant improvements in participants’ knowledge scores, increased engagement of women and youth in conservation activities, adoption of digital-based promotion strategies, enhanced organizational capacity, and stronger local leadership involvement. These outcomes highlight the contribution of integrated technological and social empowerment approaches in supporting sustainable mangrove-based ecotourism.